Prediction of Voltage Stress to Ground at Synchronous Motor Terminals in Power Drive Systems - Fritsch, Christoph; Hahn, Ingo (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe), 2023)
This paper presents an easy to parameterize simulation method to predict the voltage stress to ground at synchronous motor terminals. The simulation allows to identify critical operation speeds with highest voltage stress in amplitude and frequency. Also, the voltage stress of planned drive trains can be predicted.
CRIS-Team Scopus Importer:2024-12-16
Keywords: insulation; partial discharge; synchronous motor; Three-phase motor drive